Re-proposing Cultural Based Curriculum System of Tamansiswa as the National Education Foundation in Indonesia - Rizki Ramadhan (Journal of English Language Teaching and Islamic Integration, 2018)
The problems faced by the Indonesia educational system should have been examined deeply as it seems difficult to apply an educational system that can be implemented effectively. This issue can be seen from the number of curriculum changes recently. Considering that problems, developing educational system based on its own nation culture will be considered to be more effective in order to build the characters of the students. By developing Ki Hadjar Dewantara’s idea with his system, the educational system in Indonesia will be more practical and suitable, since this idea has been admitted as modern thought or ideas which will give a lot of beneficial for the learners